Clinical impact of novel pericoronary adipose tissue measurement on ECG-gated non-contrast chest CT scan. (3rd October 2022) - Takahashi, D; Fujimoto, S; Nozaki, Y O; Kudo, A; Kawaguchi, Y O; Takamura, K; Hiki, M; Sato, H; Tomizawa, N; Minamino, T
Abstract: Background: Pericoronary adipose tissue (PCAT) quantified from coronary computed tomography angiography (CCTA) is a new predictor of CT-derived high-risk plaque (HRP) and adverse cardiac events. There has been no report investigating the method to assess PCAT from non-contrast CT so far. In this present study, we developed a brand-new method to quantify the value of PCAT from electrocardiogram (ECG)-gated non-contrast CT (NC-PCAT). Purpose: To develop a brand-new method to quantify NC-PCAT accurately, and evaluate its prognostic value. Methods: We retrospectively studied two independent cohorts of patients undergoing CCTA and ECG-gated non-contrast CT for clinical indication of coronary artery disease (CAD). For former cohort of consecutive 300 patients, we validated the agreement between the NC-PCAT and PCAT, and evaluated the association between NC-PCAT and the prevalence of HRP. For latter cohort of consecutive 333 patients, we dichotomized them into two groups with median NC-PCAT, and assessed the prognostic value of NC-PCAT. To quantify NC-PCAT, we placed 15x15mm region of interest at epicardial fat tissue dorsally adjacent to right coronary ostium in axial slice of ECG-gated non-contrast CT, and defined NC-PCAT as the mean CT value of each 1x1mm pixel there. PCAT was quantified from CCTA using conventional method as described in former researches. Primary endpoint was defined as major adverse cardiac events (MACE), composite of all-cause death and non-fatal myocardial infarction. HRP was defined as coronary artery plaque which has two or more following features; positive remodeling, low attenuation, spotty calcification, and napkin-ring sign. Results: NC-PCAT was well-correlated with PCAT (r=0.68, p<0.0001). In former cohort, we found HRP in 34 (11.3%) patients. In multivariable logistic regression analysis, higher NC-PCAT (OR 1.06, 95% CI 1.03–1.10, p=0.0001), coronary artery calcium score (CACS) (OR 1.01 per 10 CACS increase, 95% CI 1.00–1.02, p=0.013), and current smoking (OR 2.58, 95% CI 1.03–6.49, p=0.044) were independent predictors of the prevalence of HRP. Among patients with CACS more than zero (n=193), NC-PCAT (OR 1.06, 95% CI 1.03–1.10, p=0.0002), current smoking (OR 3.02, 95% CI 1.17–7.82, p=0.027), and male (OR 2.81, 95% CI 1.06–7.48, p=0.028) were independent predictors of the prevalence of HRP, whereas CACS was not (p=0.15). In latter cohort, the median duration of follow-up was 2.9 years (IQR 1.9–3.9), and 16 (4.8%) cases of MACE were identified. The cumulative incidence of MACE was significantly higher in high NC-PCAT group. Multivariable cox hazard regression analysis revealed that higher NC-PCAT was an independent predictor of primary endpoint, even after adjustment for sex and age (HR 4.28, 95% CI 1.20–12.52, p=0.012). Conclusions: There was a positive correlation between NC-PCAT and PCAT. Higher NC-PCAT is significantly associated with not only the prevalence of HRP, but also worse clinical outcome. Funding Acknowledgement: Type of funding sources: None.